Being present for each other: long-distance video-linked seminars. - Magagna, Jeanne (Psychoanalytic Psychotherapy, 2013)
This paper describes technical issues in setting up and using long-distance learning equipment. It also describes aspects of long-distance learning during stages of the learning process and evaluations of the method. The use of the countertransference is also discussed as an important aspect of the work.